2014
DOI: 10.1039/c3cp55106g
|View full text |Cite
|
Sign up to set email alerts
|

Inner reorganization limiting electron transfer controlled hydrogen bonding: intra- vs. intermolecular effects

Abstract: In this work, experimental evidence of the influence of the electron transfer kinetics during electron transfer controlled hydrogen bonding between anion radicals of metronidazole and ornidazole, derivatives of 5-nitro-imidazole, and 1,3-diethylurea as the hydrogen bond donor, is presented. Analysis of the variations of voltammetric EpIcvs. log KB[DH], where KB is the binding constant, allowed us to determine the values of the binding constant and also the electron transfer rate k, confirmed by experiments obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The binding reactions should occur as a fast and reversible process, for which the relative rates of both dimer formation and dissociation reactions ( k f2 and k b2 ) should be very large being the system in equilibrium during the binding process. , To achieve this condition, both rate constants were fixed at values near the diffusion limit rate constant for bimolecular reactions (10 8 s –1 ) . To fully prevent kinetic limitations, a sufficiently large electron transfer standard rate constant ( k S = 100 cm s –1 ) was also supposed for simulations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding reactions should occur as a fast and reversible process, for which the relative rates of both dimer formation and dissociation reactions ( k f2 and k b2 ) should be very large being the system in equilibrium during the binding process. , To achieve this condition, both rate constants were fixed at values near the diffusion limit rate constant for bimolecular reactions (10 8 s –1 ) . To fully prevent kinetic limitations, a sufficiently large electron transfer standard rate constant ( k S = 100 cm s –1 ) was also supposed for simulations.…”
Section: Resultsmentioning
confidence: 99%
“…38,39 To achieve this condition, both rate constants were fixed at values near the diffusion limit rate constant for bimolecular reactions (10 8 s −1 ). 40 To fully prevent kinetic limitations, a sufficiently large electron transfer standard rate constant (k S = 100 cm s −1 ) was also supposed for simulations. With this information and considering the dimensionless binding parameter log(K eq C*), 38,39,41 voltammetric simulations of the mechanism involved by eqs 1 and 3 were carried out using the commercial software DigiElch 8FD.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This approach has proven useful for comparing binding abilities between structurally different anions. [17][18][19][20] The knowledge of the molecular features of the receptors has been focused. For example, Gale and co-workers 21 have reported that the acidity of the NH group of some mono-thioureas directs the anion recognition and mathematical models could predict the transmembrane transport ability.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, only a single one-electron transfer reaction is coupled sequentially with a one-proton transfer process (eqs and ). The binding reaction should occur as a fast and reversible process for which the relative rates of both formation and dissociation reactions ( k f1 and k b1 ) of the adduct (eq ) should be very large, as the system is in equilibrium during the binding process. ,, For this purpose, both rate constants were fixed at values close to the diffusion limit rate constant for a bimolecular reaction (10 8 s –1 ) . Classically, the presence of the binding reaction leads to a shift in the corresponding reduction potentials toward less negative values, exhibiting diffusion-controlled voltammetric waves. ,,, This case can be identified as a DE process …”
Section: Results and Discusionmentioning
confidence: 99%
“…From the above discussion, more information is required about the conditions driving H-bonded systems into proton transfer reactions to fully understand anion recognition processes by these urea derivatives. Also, such a study would complement the growing interest in elucidating H-bonding effects on PCET reactions. ,, Dihomooxacalix[4]­arene bidentate ureas are interesting H-bond donor species ((HD) 2 -R 2 ) for studying anion recognition, as previous results have shown that they noticeably increase their binding capacity to anions when the nature of the substituent groups in their structures is changed (from t -Bu to Ph, K b ranges from ∼250 to ∼7000 M –1 , respectively). , Also, by electrogenerating dianions ([NO 2 – ϕ – NO 2 ] 2– ) from dinitrobenzene compounds (NO 2 – ϕ – NO 2 ), electron transfer-controlled hydrogen bonding (ETCHB) can be studied, , leading to increases in the binding affinity when the charge state of the receptor is changed. ,,, ETCHB processes between these latter species can be generally described by the next set of chemical equations: , …”
Section: Introductionmentioning
confidence: 99%